Predicting the impact of feed spacer modification on biofouling by hydraulic characterization and biofouling studies in membrane fouling simulators. (1st March 2017) - Siddiqui, A.; Lehmann, S.; Bucs, Sz. S.; Fresquet, M.; Fel, L.; Prest, E.I.E.C.; Ogier, J.; Schellenberg, C.; van Loosdrecht, M.C.M.; Kruithof, J.C.; Vrouwenvelder, J.S.
Abstract: Feed spacers are an essential part of spiral-wound reverse osmosis (RO) and nanofiltration (NF) membrane modules. Geometric modification of feed spacers is a potential option to reduce the impact of biofouling on the performance of membrane systems. The objective of this study was to evaluate the biofouling potential of two commercially available reference feed spacers and four modified feed spacers. The spacers were compared on hydraulic characterization and in biofouling studies with membrane fouling simulators (MFSs). The virgin feed spacer was characterized hydraulically by their resistance, measured in terms of feed channel pressure drop, performed by operating MFSs at varying feed water flow rates. Short-term (9 days) biofouling studies were carried out with nutrient dosage to the MFS feed water to accelerate the biofouling rate. Long-term (96 days) biofouling studies were done without nutrient dosage to the MFS feed water. Feed channel pressure drop was monitored and accumulation of active biomass was quantified by adenosine tri phosphate (ATP) determination. The six feed spacers were ranked on pressure drop (hydraulic characterization) and on biofouling impact (biofouling studies). Significantly different trends in hydraulic resistance and biofouling impact for the six feed spacers were observed. The same ranking for biofouling impact on the feed spacers was found for the (i) short-term biofouling study with nutrient dosage and the (ii) long-term biofouling study without nutrient dosage. The ranking for hydraulic resistance for six virgin feed spacers differed significantly from the ranking of the biofouling impact, indicating that hydraulic resistance of clean feed spacers does not predict the hydraulic resistance of biofouled feed spacers. Better geometric design of feed spacers can be a suitable approach to minimize impact of biofouling in spiral wound membrane systems. Graphical abstract: Highlights: Hydraulics and biofouling study of six different feed spacers. Short and long-term biofouling study with and without nutrient dosage. Same ranking of spacer performance for short-term and long-term biofouling study. Hydraulic resistance of clean spacer not predictive of biofouled spacer performance. Geometric modification of feed spacers can be used to minimize biofouling impact.